Pericardial Involvement in ST-Segment Elevation Myocardial Infarction as Detected by Cardiac MRI - Massalha, Eias; Brodov, Yafim; Oren, Daniel; Fardman, Alex; Natanzon, Sharon Shalom; Mazin, Israel; Beinart, Roy; Goldkorn, Ronen; Konen, Eli; Segni, Elio Di; Segev, Amit; Beigel, Roy; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Post myocardial infarction pericarditis is considered relatively rare in the current reperfusion era. The true incidence of pericardial involvement may be underestimated since the diagnosis is usually based on clinical and echocardiographic parameters. Objectives This study aims to document the incidence, extent, and prognostic implication of pericardial involvement in ST-segment elevation myocardial infarction (PISTEMI) using cardiac MRI (CMR). Methods One hundred and eighty-seven consecutive ST-segment elevation myocardial infarction patients underwent CMR on day 5 ± 1 following admission, including steady-state free precession (SSFP) and late Gadolinium enhancement (LGE) sequences. Late Gadolinium enhancement and microvascular obstruction (MVO) were quantified as a percentage of left ventricular (LV) mass. Late Gadolinium enhancement was graded for transmurality according to the 17 AHA left ventricle (LV) segment model (LGE score). Late pericardial enhancement (LPE), the CMR evidence of pericardial involvement, was defined as enhanced pericardium in the LGE series and was retrospectively recorded as present or absent according to the 17 AHA segments. Late pericardial enhancement was evaluated adjacent to the LV, the right ventricle, and both atria. Clinical, laboratory, angiographic, and echocardiographic data were collected. Clinical follow-up for major adverse cardiac events (MACE) was documented and correlated with CMR indices, including LGE, MVO, and LPE. Results Late pericardial enhancement (LPE+) was documented in 77.5% of the study cohort. A strong association was found between LPE and the degree and extent of myocardial injury (LGE, MVO). Both LGE and MVO were significantly correlated with increased MACE on follow-up. On the contrary, LPE presence, either adjacent to the LV or the other cardiac chambers, was associated with a lower MACE rate in a median of 3 years of follow-up HR 0.39, 95% CI (0.21–0.7), p = 0.002, and HR 0.48, 95% CI (0.26–0.9), p = 0.02, respectively. Conclusions Prognostic implication of pericardial involvement in ST-segment elevation myocardial infarction was documented by CMR in 77.5% of our STEMI cohort. Late pericardial enhancement presence correlated significantly with the extent and severity of the myocardial damage. Unexpectedly, it was associated with a considerably lower MACE rate in the follow-up period.